2020
DOI: 10.3390/ijms21082746
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of ACTB and ACTG1 with CRISPR/Cas9(D10A) Technique Shows that Non-Muscle β and γ Actin Are Not Equal in Relation to Human Melanoma Cells’ Motility and Focal Adhesion Formation

Abstract: Non-muscle actins have been studied for many decades; however, the reason for the existence of both isoforms is still unclear. Here we show, for the first time, a successful inactivation of the ACTB (CRISPR clones with inactivated ACTB, CR-ACTB) and ACTG1 (CRISPR clones with inactivated ACTG1, CR-ACTG1) genes in human melanoma cells (A375) via the RNA-guided D10A mutated Cas9 nuclease gene editing [CRISPR/Cas9(D10A)] technique. This approach allowed us to evaluate how melanoma cell motility was impacted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 66 publications
5
39
1
Order By: Relevance
“…In one of our previous experiments, we observed that the cells lacking β-or γ-actin had changed the formation of focal adhesions (FAs) 8 . That is why we evaluated the impact of ACTBL2 knockout on FAs formation.…”
Section: Knockout Of Actbl2 Led To the Pronounced Formation Of Focal mentioning
confidence: 92%
See 2 more Smart Citations
“…In one of our previous experiments, we observed that the cells lacking β-or γ-actin had changed the formation of focal adhesions (FAs) 8 . That is why we evaluated the impact of ACTBL2 knockout on FAs formation.…”
Section: Knockout Of Actbl2 Led To the Pronounced Formation Of Focal mentioning
confidence: 92%
“…The functional diversification of non-muscle isoactins and their subcellular localization is still under active research. Recently, we reported that β-and γ-actin are non-redundant regarding their involvement in 2D and 3D motility and focal adhesion formation of human melanoma cells 8 . In one of our earlier studies 9 , we obtained data showing that gelsolin, one of the many actin-binding proteins (ABPs), interacts specifically with β-actin-like protein 2 (actbl2) in human melanoma cells.…”
Section: Pmamentioning
confidence: 99%
See 1 more Smart Citation
“…It is even unclear whether in cells pure filaments of individual forms exist because in vitro it has been shown that both cytoplasmic actins form copolymers (Muller et al, 2013) and the subcellular localization experiments provided evidence for mixed areas in cells where two types of actins are present. A nice example of this is shown in Figure 1 of Malek et al (2020).…”
Section: Functionsmentioning
confidence: 98%
“…However, mouse embryonic fibroblasts (MEFs) lacking β-actin can migrate if treated with ROCK-inhibitor suggesting that γ-actin (or α-smooth muscle actin) is also capable of driving cell migration (Tondeleir et al, 2012). Similarly, A375 melanoma devoid of β-actin had the same velocity as control cells in 2D migration experiments, whereas these cells lacking γ-actin migrated more slowly (Malek et al, 2020). β-Actin protein has also been located in the nucleus (Falahzadeh, Banaei-Esfahani, & Shahhoseini, 2015), suggesting a role in gene expression, transcription and epigenetic regulation in the nucleus (Hofmann et al, 2004;Olson & Nordheim, 2010;Visa & Percipalle, 2010;Xu, Thuraisingam, Morais, Rola-Pleszczynski, & Radzioch, 2010;Zheng, Han, Bernier, & Wen, 2009).…”
Section: Functionsmentioning
confidence: 99%